Knock Knock : My Dad's Dream For Me - Beaty, Daniel; Collier, Bryan (New York Little, Brown and Company, 2013)
"A boy wakes up one morning to find his father gone. At first, he feels lost. But his father has left him a letter filled with advice to guide him through the times he cannot be there"--
Keywords: Fathers and sons -- Juvenile fiction; Separation (Psychology) -- Juvenile fiction; African Americans -- Juvenile fiction; Fathers and sons -- Fiction; Separation (Psychology) -- Fiction; African Americans -- Fiction